Market, exploration and colonization. The epistemological roots of the utilitarian knowledge of modern Geography - Martínez-Álvarez, Héctor Ignacio (2019)
This article seeks to investigate the main historical, theoretical and political elements that marked the origin of the so-called Modern Geography from the philosophical, epistemological and methodological exploration that modern science advanced and its pragmatic and utilitarian usefulness in the process of shaping the capitalist world market, particularly in the process of colonization. Unlike previously written works on the subject matter, the present exposition emphasizes the legitimating role that knowledge and geographical practices had upon the transition from feudal to capitalist society, specifically the rise and consolidation of the bourgeoisie.